A selected review on the negative externalities of the freight transportation: Modeling and pricing. (May 2015) - Demir, Emrah; Huang, Yuan; Scholts, Sebastiaan; Van Woensel, Tom
Highlights: A systematic review of publications on the negative externalities is carried out. Several mathematical modeling approaches of the negative externalities are discussed. The literature of available studies looking at pricing of the negative externalities is investigated. Abstract: The planning of freight transportation activities creates benefits as well as costs. Among those costs, some of them, namely externalities, fall on other people/society that have no direct relevance to the operations of transportation. Such externalities are accrued expenses which should be addressed by actual pricing policies to enable an efficient and sustainable freight transportation system. This paper reviews externalities in quantitative terms, and then provides pricing studies of these costs per unit of freight transported along with the most recent estimations. The associated negative externalities are structured by transportation mode (road, rail, maritime, and air).